Evaluating the Application of Components Governance and Culture Based on COSO ERM at Pt. Agro - Yuwono, Matias Andika; Ellitan, Lena (UUM Press, 2024)
This article explores the effective establishment of governance and corporate culture within companies by implementing the Committee of Sponsoring Organizations of the Treadway Commission (COSO) Enterprise Risk Management (ERM). Utilizing COSO ERM provides an understandable framework for shaping corporate governance, defining company strategy, instilling culture and values, and appreciating competent employees. The study demonstrates that companies implementing COSO ERM’s governance and culture components can attain their anticipated goals by minimizing potential risks. By employing a qualitative case study analysis, researchers explored the topic in depth; the research focuses on PT. Agro, revealing its successful implementation of COSO ERM’s governance and culture components. The findings showcase PT. Agro established robust directorial supervision, an effective assessment system, adoption of a three-line organizational structure prioritizing risk control, and cultivation of an influential work culture through applying the BISA culture and IACE company values. The article emphasizes the significance of employees as valuable assets for companies, with PT. Agro consistently develops competent individuals for mutual benefit. Through ongoing training, skill-building workshops, and mentorship programs, PT. Agro invests in its workforce, fostering a culture of excellence and innovation. This commitment strengthens internal capabilities and nurtures employee satisfaction and loyalty. This study contributes to the limited discussion on the COSO ERM governance and culture components, providing a detailed exploration of the five principles and serving as a valuable material for future research in other companies